Congenital adhesion bands causing distal duodenal obstruction in a 6-year old child - Elroy Patrick Weledji; Naiza Monono (Elsevier, 2021)
A congenital adhesion band is a rare condition, but may induce small bowel obstruction at any age. Only a few sporadic case reports exist. We report a 6 -year- old boy with failure to thrive who presented with symptoms of high small bowel obstruction, absolute constipation of one week duration. He was managed successfully by division of congenital adhesion bands running across the third part of the duodenum. A good result can be expected in a late presentation of a congenital adhesive intestinal obstruction if early diagnosis and prompt management is pursued.